2021
DOI: 10.3390/ijerph18073756
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Clinical Applications of CAD/CAM Technology for Craniofacial Implants Placement and Manufacturing of Nasal Prostheses

Abstract: The aim of this systematic review was to gather the clinical and laboratory applications of CAD/CAM technology for preoperative planning, designing of an attachment system, and manufacturing of nasal prostheses. According to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, an electronic search was carried out. Only human clinical studies involving digital planning for the rehabilitation of facial defects were included. A total of 21 studies were included with 23 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…These digital technology advancements further led to the guided surgeries of craniofacial implants and assisted clinicians and dental technicians in exploring the possibilities of the designing and printing of molds, retentive substructures, customized implants, models, digital wax-ups and prosthesis fabrication [18]. With CAD/CAM application, the surgical procedures became more predicable and reduced the clinical and laboratory times of the surgical and prosthetic steps, reduced the number of patient appointments and provided the patients a chance to virtually visualize the expected outcome before undergoing irreversible procedures [18]. Therefore, the aim of this paper was to gather clinical studies about the various applications of CAD/CAM technology for craniofacial implants placement and the fabrication of orbital prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These digital technology advancements further led to the guided surgeries of craniofacial implants and assisted clinicians and dental technicians in exploring the possibilities of the designing and printing of molds, retentive substructures, customized implants, models, digital wax-ups and prosthesis fabrication [18]. With CAD/CAM application, the surgical procedures became more predicable and reduced the clinical and laboratory times of the surgical and prosthetic steps, reduced the number of patient appointments and provided the patients a chance to virtually visualize the expected outcome before undergoing irreversible procedures [18]. Therefore, the aim of this paper was to gather clinical studies about the various applications of CAD/CAM technology for craniofacial implants placement and the fabrication of orbital prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Bi, Y. et al, 2013 [35] claimed that the whole digital workflow for an orbital prosthesis took 18.5 h from data acquisition to delivery of the prosthesis. Furthermore, a systematic review from Tanveer, W. et al [18] also mentioned the digital workflow times of different case studies, which were found to be in the range of 12-21 h. However, CAD/CAM systems do pose the limitations of skilled technical staff and expensive equipment hindering their use in many parts of the world. The printing of a direct silicone prosthesis and color matching are other limitations that might be resolved with further digital advancements in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, digital technology is becoming widely used in the field of oral implantation [6,7]. The accuracy of the implant position and depth after using the implant guide plate positioning is the subject of much research worldwide [8].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of frameworks or copings range from single-tooth restorations to 14-unit bridges (Figure 1) [9]. Furthermore, in the meantime, CAD/CAM-based removable dentures have been produced [10]. The preparation is usually scanned.…”
Section: Introductionmentioning
confidence: 99%